PRINCIPALSâ€™ PERCEPTIONS OF GUIDANCE AND COUNSELLING SERVICES IN KWARA STATE SECONDARY SCHOOLS, NIGERIA: IMPLICATION FOR STAKEHOLDERS - Suleiman, Yusuf; Hanafi, Zahyah; Kamil, Lasisi Adekola; Bosede, Famolu Florence (Departemen Psikologi Pendidikan dan Bimbingan FIP Universitas Pendidikan Indonesia, 2021)
Students are often faced with numerous challenges, which can bring on stress, anxiety, depression or relationship problems with those around them. Because of the foregoing, this study examined the principalsâ€™ perception of guidance and counselling in secondary schools. The study population consist of all principals in secondary schools in Kwara State, Nigeria. Non-probability sampling techniques (stratified, purposive and convenience) were employed to select 20 principals to participate in the study. An instrument titled â€œInterview Guide on Guidance and Counselling Services (IGGCS)â€ was used to collect relevant data from the principals while secondary data were obtained from the counselling department of the schools. Nvivo software (version 10) was used to analyse the data collected. The findings of the study revealed that principals believe the provision of counselling services had a significant impact on student's academic achievement, even though most of the secondary schools do not have a good counselling unit, qualified counsellors, and counselling facilities. This study recommends that a well-equipped counselling unit should be available in schools. Only certified counsellors should be deployed to offer counselling services to students. Lastly, students should be sensitized and encouraged by the school on the need for them to go for counselling to solve their numerous challenges.Â Â Â Â Â Â Â